Reading the Hebrew Bible with animal studies - Stone, Ken 1962- (Stanford, CA Stanford University Press, 2020)
Animal studies may be a recent academic development, but our fascination with animals is nothing new. Surviving cave paintings are of animal forms, and closer to us, as Ken Stone points out, animals populate biblical literature from beginning to end. This book explores the significance of animal studies for the interpretation of the Hebrew Bible. The field has had relatively little impact on biblical interpretation to date, but combined with biblical scholarship, it sheds useful light on animals, animal symbolism, and the relations among animals, humans, and God—not only for those who study biblical literature and its ancient context, but for contemporary readers concerned with environmental, social, and animal ethics. Without the presence of domesticated and wild animals, neither biblical traditions nor the religions that make use of the Bible would exist in their current forms. Although parts of the Bible draw a clear line between humans and animals, other passages complicate that line in multiple ways and challenge our assumptions about the roles animals play therein. Engaging influential thinkers, including Jacques Derrida, Donna Haraway, and other experts in animal and ecological studies, Reading the Hebrew Bible with Animal Studies shows how prehumanist texts reveal unexpectedly relevant dynamics and themes for our posthumanist age
Frontmatter -- Contents -- Acknowledgments -- Introduction -- 1. Israel’s Companion Species and the Creation of Bibles -- 2. Tracking the Dogs of Exodus -- 3. The Chimera of Biblical Sacrifice -- 4. From Animal Hermeneutics to Animal Ethics -- 5. Israel’s Wild Neighbors in the Zoological Gaze -- 6. The Psalmist, the Primatologist, and the Place of Animals in Biblical Religion -- 7. Reading the Hebrew Bible in an Age of Extinction -- Notes -- Index
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Keywords: Animal welfare -- Biblical teaching; Animals in the Bible; Animals -- Religious aspects; RELIGION / Biblical Studies / Old Testament